Bioethanol Production by Using Detoxified Sugarcane Bagasse Hydrolysate and Adapted Culture of Candida tropicalis - Inda Setyawati; Laksmi Ambarsari; Siti Nur'aeni; Suryani Suryani; Puspa Julistia Puspita; Popi Asri Kurniatin; Waras Nurcholis (Current Biochemistry, 2015)
Ethanol is considered as the most promising alternative fuel, since it can be produced from a variety of agriculturally-based renewable materials, such as sugarcane bagasse. Lignocellulose as a major component of sugarcane bagasse is considered as an attractive renewable resource for ethanol production due to its great availability and relatively low cost. The major problem of lignocellulose is caused by its need for treatment to be hydrolyzed to simple sugar before being used for bioethanol production. However, pretreatment using acid as hydrolyzing agent creates some inhibitor compounds that reduce ethanol production because these compounds are potential fermentation inhibitors and affect the growth rate of the yeast. Reduction of these by-products requires a conditioning (detoxification and culture starter adaptation). Thus, the aim of this study was to evaluate bioethanol production by fermentation with and without detoxified sugarcane bagasse acid hydrolysate using adapted and non-adapted culture of C. tropicalis. According to this study, the highest ethanol amount was obtained about 0.43 % (v/v) with an ethanol yield of 2.51 % and theoretical yield of 4.92 % by fermentation of sugarcane bagasse hydrolysate with detoxification using the adapted strain of C. tropicalis at 72 hours fermentation time. Furthermore, the addition of 3 % glucose as co-substrate on detoxified-hydrolysate media only achieved the highest ethanol concentration 0.21 % after 24 hours fermentation with the ethanol yield 0.69 % and theoretical ethanol yield 1.35 %, thus it can be concluded that the addition of glucose could not increase the ethanol production.